2023
DOI: 10.1021/acsestengg.3c00042
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Direct Electron Transfer Regime of Peracetic Acid Activation: Quantitative Structure–Activity Relationship Analysis of Carbon Nanotube Catalysis

Abstract: The demands for high-efficient and green activation of peracetic acid (PAA) have triggered research in exploring carbon catalysis. Nevertheless, the efforts in designing reaction-oriented and high-performance carbon catalysts are largely impeded by an ambiguous understanding of the fundamental carbon structure–PAA activation performance relationship. Herein, we investigated the quantitative structure–activity relationship (QSAR) of carbon nanotubes (CNTs) for PAA activation and micropollutant (MP) removal, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Carbon nanotubes (CNTs), as an emerging carbon material, have recently received increasing attention for the abatement of aqueous pollutants. Several studies have shown that CNTs exhibit excellent activity toward various oxidants (e.g., permanganate, persulfate, peracetic acid). Yun et al studied the activation of peroxydisulfate (PDS) by CNTs and found that CNTs could also activate PI . Despite some enlightening results on the system of PI activation by CNTs, the intrinsic nature of the oxidation process remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs), as an emerging carbon material, have recently received increasing attention for the abatement of aqueous pollutants. Several studies have shown that CNTs exhibit excellent activity toward various oxidants (e.g., permanganate, persulfate, peracetic acid). Yun et al studied the activation of peroxydisulfate (PDS) by CNTs and found that CNTs could also activate PI . Despite some enlightening results on the system of PI activation by CNTs, the intrinsic nature of the oxidation process remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Then, electrochemical analyses were conducted to elucidate the electron transfer process among Cu NCs/HAp, H 2 O 2 , and MB. It was observed that the addition of H 2 O 2 led to an increase in current density compared to the control group (Figure C,D), indicating the occurrence of electron transfer between 3-CuNCs/HAp and H 2 O 2 . , However, upon further addition of MB, it was inferred that there was no direct reaction between 3-Cu NCs/HAp and MB. Hence, it is likely that 1 O 2 and • OH originated from the transformation of • O 2 – and Cu 0 /Cu + /Cu 2+ in the Cu NCs/HAp + H 2 O 2 system.…”
Section: Resultsmentioning
confidence: 91%
“…Metal-free carbonaceous materials have emerged as promising alternatives in environmental catalysis to boost PAA activation by virtue of easy availability, high conductivity, and nontoxicity. To date, carbon nanotube, , reduced graphene oxide, activated carbon, and biochar , have been adopted for PAA activation and displayed satisfactory reactivity in pollutant elimination via either a radical or nonradical pathway. However, there are still three challenging issues that need to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies emphasized 1 O 2 as the primary contributor to pollutant oxidation according to the inhibition of pollutant degradation with the addition of common quenchers like furfuryl alcohol (FFA) and l -histidine ( l -his). However, these quenchers have been also reported to react with other reactive species such as the carbon-PAA complex , or directly react with PAA . (ii) The intrinsic active sites on carbon catalysts remain ambiguous due to the intricate carbon molecular structures and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation